Polemik Pernikahan Beda Agama dalam Tinjauan Hukum Profetik - Muhammad Solikhudin (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
This writing attempts to lift about polemic of interfaith marriage that occurred in Indonesia, where in the real some people want to legalize interfaith marriage. This is a necessity that occurred in the era of democracy that leads to free of speech. Looking at the phenomenon that leads to the understanding that interfaith marriage should be seen by point of view that more wide while utilizing common sense, so virtue appears is developed and perpetuated together constantly-at the same time design-building democracy isn’t marred from the original. In this case democracy is directed as a system that seeks to freedom with logical limit. But the reality democracy is distorted in the nation’s life deliberately. The issue appears lies in the effort to legalize interfaith marriage in order to realize the nuances of equality. Offer grounding and enforcement law prophetic show significance to be retained and developed together in here. Therefore in this writing will be revealed polemic of interfaith marriage with point of view prophetic law.